1995
DOI: 10.1111/j.1365-2249.1995.tb03474.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical Report: results of immunological tests on faecal extracts are likely to be extremely misleading

Abstract: SUMMARYClinical investigation of gut immunity is difficult because of the need to study intestinal tissues or secretions directly. Others have reported that immunoglobulins, antibodies and cytokines can be detected in saline extracts of faeces. We have assessed the validity of this approach by measuring immunoglobulins, albumin, a|-antitrypsin and isotype-specific antibodies in matched samples of faeces and whole gut lavage fluid. Results were compared as estimated output per day, and by using haemoglobin as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Up to 70 times more IgA can be purified from feces compared to secretions collected by rectal swabs. The use of fecal extracts for monitoring mucosal IgA in the gastrointestinal tract has been criticized as unrepresentative of amounts present in whole gut lavages [52]. However, this previous study did not purify IgA.…”
Section: Discussionmentioning
confidence: 96%
“…Up to 70 times more IgA can be purified from feces compared to secretions collected by rectal swabs. The use of fecal extracts for monitoring mucosal IgA in the gastrointestinal tract has been criticized as unrepresentative of amounts present in whole gut lavages [52]. However, this previous study did not purify IgA.…”
Section: Discussionmentioning
confidence: 96%
“…Methods for obtaining this type of sample from mice include intestinal lavage (Elson et al, 1984;Grewal et al, 2000;O'Mahony et al, 1990), extraction of fecal samples (deVos and Dick, 1991;Grewal et al, 2000), or sampling with Polyfiltronics wicks (Haneberg et al, 1994). Fecal extracts have been used as a substitute for the laborious lavages and directly sampled intestinal specimens but the validity of this approach has been questioned (Ferguson et al, 1995). However, when samples obtained by these techniques were compared for contamination with Igs derived from the blood circulation ( Meckelein et al, 2003), the lowest levels of plasma-derived IgA were found in feces, followed by intestinal lavages, and the highest levels were in filter wick-collected samples.…”
Section: Intestinal Secretionsmentioning
confidence: 99%
“…In some studies, fecal extracts have been used for measurement of intestinal antibodies. However, the use of such specimens should be discouraged because of the precipitous decline of immunoglobulins because of their rapid digestion by fecal proteases and the limited information obtainable (Ferguson et al, 1995).…”
Section: Intestinal Secretionsmentioning
confidence: 99%